The effects of turnover on expert effort estimation - Karna, Hrvoje (Array, 2020)
Turnover of the personnel represents a serious issue for management of software projects. The buildup of competences and phasing in of the people into the project requires both time and effort. This paper presents a case study of a large in-house agile software development project. The research goal was to determine the effects that turnover has on the expert effort estimation. In order to do this, paper examines relations across empirical data on a studied project. Study findings are the following: a) it is necessary to distinguish types of turnover, b) the general and planned turnover do not necessarily have a negative effect on estimation accuracy, and c) the unplanned turnover can have a significant negative impact on the reliability of the estimates and therefore should be treated with special attention. Results suggest that these facts should be taken into account both by the management and human resources.